Anas won 3rd place in Prime Minister Cup’s International Malay Debate 2016 - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) international student Anas Mohamad Husain Kassim, who is from Iraq, won third place in the Prime Minister Cup’s International Malay Debate 2016 (PABM) that was held in Putrajaya International Convention Centre (PICC), Putrajaya on March 26, 2016.